Answer: y = 5/2x + 6
Step-by-step explanation:
y - y₁ = m(x - x₁)
y - (-9) = 5/2(x- (-6))
y + 9 = 5/2(x+ 6)
y +9 = 5/2x + 15
y = 5/2x + 15 - 9
y = 5/2x +6
Answer:is an expression telling the computer what mathematical operation to perform upon a specific value. When referring to computer software, formulas are most often used in spreadsheet programs, such as Microsoft Excel.
Step-by-step explanation:
Answer: 9
Step-by-step explanation: just devide then times
Step-by-step explanation:
✓(-1/6×4/7)+(-1/6×-2/5)
✓(-4/42)+(2/30)
✓(-2/21)+(1/15)
✓(-2/21+1/15)
=-<u>1/35</u>
Answer:
x^2 = 121
x = 11 Im wanting brainliest
Step-by-step explanation: